KESIAPAN MENJADI CALON GURU DAN FAKTOR YANG MEMPENGARUHINYA - Rezki Andika; Suarman Suarman; Henny Indrawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2023)
Abstract: This study aims to analyze the readiness of students to become prospective teachers and the factors that influence it. This study used a mixed method technique. The subjects of this study were all students of the Economics Education Study Program FKIP University of Riau, academic year of 2017 with a total of 78 people. Data collection methods were questionnaires and interviews. Data were analyzed using descriptive analysis technique. The results showed that students of the Economics Education Study Program, FKIP, University of Riau were not ready to become prospective professional teachers. The readiness of students in pedagogic competence is in the quite ready category. Meanwhile, in term of professional competence, students of the Economics Education Study Program FKIP University of Riau were not ready to become prospective professional teachers. Judging from the factors that influence student readiness, all factors, both internal and external, greatly influence student readiness, except for physical conditions.